1993
DOI: 10.1897/1552-8618(1993)12[1059:dooppe]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Organochlorine Pesticides, Particularly Endosulfan, by Trichoderma Harzianum

Abstract: A fungus, Trichoderma harzianum, was found to degrade DDT, dieldrin, endosulfan, pentachloronitrobenzene, and pentachlorophenol but not hexachlorocyclohexane. The fungus degraded endosulfan under various nutritional conditions throughout its growth stages. Endosulfan sulfate and endosulfan diol were detected as the major fungal metabolites of endosulfan. Piperonyl butoxide, when added to the growth medium, completely inhibited the endosulfan degradation. Din-propyl malaoxon also inhibited the overall endosulfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
2
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 23 publications
1
54
2
1
Order By: Relevance
“…Decomposition of xenobiotics by the genus Trichoderma was first reported in Trichoderma viride by Baarschers et al in 1986 (31). A large portion of toxic xenobiotics, such as endosulfan (32), cyanide pollutants (33), dichlorvos (34), and even heavy metals (35), are removed from polluted environments by the genus Trichoderma. The potent capacity of the genus to degrade various xenobiotics is due to both extracellular and intracellular metabolic pathways catalyzed by both specific and nonspecific enzymatic systems.…”
Section: Discussionmentioning
confidence: 99%
“…Decomposition of xenobiotics by the genus Trichoderma was first reported in Trichoderma viride by Baarschers et al in 1986 (31). A large portion of toxic xenobiotics, such as endosulfan (32), cyanide pollutants (33), dichlorvos (34), and even heavy metals (35), are removed from polluted environments by the genus Trichoderma. The potent capacity of the genus to degrade various xenobiotics is due to both extracellular and intracellular metabolic pathways catalyzed by both specific and nonspecific enzymatic systems.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, basidiomycetes show more resistance toward these compounds (Gomes Machado et al, 2005;Rigas et al, 2005). Recently it is reported that a strain of Trichoderma harzianum has capability to degrade organochlorines through an oxidative system (Katayama and Matsumura, 2009).…”
Section: Organochlorine Pesticide and Their Degradationmentioning
confidence: 99%
“…They produces intracellular or extra cellular enzymes such as hydrolytic enzymes, oxygenases, peroxidases (Van Eerd et al, 2003).The basidiomycetes are more resistant to these compounds (Gomes Machado et al, 2005;Rigas et al, 2005). Recently a strain of Trichoderma harzianum is reported to degrade organochlorines through an oxidative system (Katayama and Matsumura, 2009).…”
Section: Microbial Enzyme Systems In Pesticide Biodegradationmentioning
confidence: 99%
“…Among these, basidiomycetes seem to be more resistant to these compounds (Gomes Machado et al, 2005;Rigas et al, 2005). Recently a strain of Trichoderma harzianum has also been shown to degrade organochlorines through an oxidative system (Katayama & Matsumura, 2009). …”
Section: Organochlorinesmentioning
confidence: 99%